The Path Toward Achieving Good Health and Well-Being (SDG 3) through Quality Education (SDG 4) - Ahmad, Wafa; Sasa, Tala; Bahtiti, Nawal H.; khuzai, Rula; Rahman, Ibrahim Abdel- (International Journal of Membrane Science and Technology, 2023)
The Sustainable Development Goals (SDGs) call for all countries to achieve 17 broad development goals by 2030. One of the ways to achieve good health and well-being is health awareness to prevent diseases through high-quality education. This study aims to measure environmental awareness among Applied Science Private University (ASU) students in Jordan to attain good health and well-being. A cross-sectional questionnaire was conducted in 2022 containing 11 statements to measure students' health knowledge that contributes to disease prevention and its relationship to environmental pollution. The 11 statements within the study were subjected to mean and standard deviation summary analysis. The Mann-Whitney test was applied to determine students' environmental awareness to reach well-being concerning gender, age, and college. The sample involved 151 students from (ASU), 32.5 % of them are male students while the remaining (67.5 %) are females; 57 % are from scientific colleges while the remaining (43 %) are from humanities colleges, and 53 % are with ages greater than or equal to 20 years old, while the remaining (47 %) are with ages less than 20 years old. According to the results, students had a medium environmental awareness to reach well-being with a mean value of 2.1427 and a value of 0.30014 as standard deviation. Male students had higher environmental awareness reach well-being than females. Humanities colleges students had greater environmental awareness to reach well-being than scientific colleges students.